PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MEMBACA PARGRAF SISWA KELAS IV SD NEGERI 034 TARAIBANGUN - Yurike, Yurike; Kurniaman, Otang; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the effect of Cooperative Integrated Reading and Composition (CIRC) learning model on the ability to read paragraphs of Elementary School students 034 Taraibangun. The sample in this research is class IVA as experiment class which amount to 38 students, and class IVC as control class which amounted to 40 students. The method used in this research is the experimental method (Quasi Experimental design) with the research design is nonequivalent control group design. The instrument of this research is a multiple choice of 25 items that will be used as a data collection tool. There is a significant difference in the reading ability of the paragraph between the experimental class and the control class. In the experimental class by applying the average CIRC model of pretest 35.37 to 84.94 on the posttest with an average gain increase of 0.756 with strong category. While in the control class with ordinary learning there is also an increase from the average of 41.30 to 77.20 on the posttest with an average gain increase of 0.609 with the medium category. Big influence seen from the research data correlation coefficient of 0.803 with very strong category, sehinggan CIRC learning model affect the ability to read paragraphs of students by 64.5% while 35.5% reading ability paragraphs students are influenced by other factors.Keywords: CIRC Learning Model, Reading Paragraph